2018
DOI: 10.1016/j.drugalcdep.2018.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transitions across stages of heroin use and dependence prior to treatment-seeking among people in treatment for opioid dependence

Abstract: In this treatment sample, onset of heroin use occurred during late adolescence, suggesting the need for targeted interventions in mid-adolescence. Transitions to heroin dependence, then treatment-seeking, occurred during early adulthood. Rapid transitions from use to dependence were associated with younger birth cohorts, greater exposure to childhood maltreatment, and later onset of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…On the other hand, the mean age at onset of heroin exposure (35.6 years) was much older than in a previous study in Australia (18 years). 43 However, previous studies have also reported an older age at onset of heroin use ranging from 25 to 30 years in Taiwan, 44 , 45 which is closer to our report. Differences in social culture may contribute to the difference between Taiwan and other countries.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the mean age at onset of heroin exposure (35.6 years) was much older than in a previous study in Australia (18 years). 43 However, previous studies have also reported an older age at onset of heroin use ranging from 25 to 30 years in Taiwan, 44 , 45 which is closer to our report. Differences in social culture may contribute to the difference between Taiwan and other countries.…”
Section: Discussionsupporting
confidence: 87%
“…Research on trajectories of drug use has most often considered the transition between use and dependence 1,2 or focused on specific populations such as people in treatment for DUDs 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Observation commenced on the date exactly 4 years before first entering OAT and ended on Dec 31, 2011, or the date of death, whichever was earlier. Charge rates could therefore be compared over a minimum 1-year period after initial entry into OAT (except in the case of death), while establishing a baseline charge history in the 4 years immediately before OAT entry (representing the average time lag before an individual enters treatment after becoming opioid dependent in NSW 23 ). Ongoing opioid dependence was also assumed following first entry into OAT, given that opioid dependence is a chronic relapsing disorder with low remission rates.…”
Section: Methodsmentioning
confidence: 99%